Longitudinal Trajectory of Free Fatty Acids in Pregnancy According to First-Trimester Maternal Metabolic Status and the Presence of Gestational Diabetes - Otilia Perichart-Perera; Isabel González-Ludlow; Omar Piña-Ramírez; Maricruz Tolentino-Dolores; Guadalupe Estrada-Gutierrez; Sandra B. Parra-Hernández; Maribel Sánchez-Martínez; Omar Granados-Portillo; Ameyalli M. Rodríguez-Cano (Metabolites)
Background/Objectives: Maternal free fatty acids (FFAs) play a critical role in maternal metabolism, fetal growth, and pregnancy outcomes. However, their relationship with maternal metabolic status in early pregnancy and the subsequent development of gestational diabetes mellitus (GDM) remains unclear. Aim: Assess the trajectory of FFA concentrations during pregnancy, considering first-trimester metabolic status (obesity, insulin resistance—IR) and the development of GDM, and evaluate whether first-trimester FFA is a relevant risk factor for GDM. Methods: A case–control study nested within the OBESO cohort (Mexico City, pregnant women and their children), classified women according to first-trimester metabolic status (pregestational body mass index—pBMI, insulin resistance homeostasis model assessment—HOMA-IR > 1.6), as well as the presence of GDM: Group 1 (normal weight without IR, n = 60), Group 2 (obesity without IR, no GDM, n = 20), Group 3 (obesity with IR, no GDM, n = 20), and Group 4 (obesity with IR, with GDM, n = 9). FFA concentrations were measured each trimester. Statistical analyses included repeated measures ANOVA and logistic regression models. Results: FFA concentrations were the highest in Group 4 across all trimesters (p < 0.05). FFAs decreased throughout pregnancy in all groups (p = 0.023), with the most significant decline from the first to the third trimester (p < 0.001). The greatest reduction occurred in Group 4 (p < 0.001), followed by Group 3. Multivariate logistic regression showed no association between first-trimester FFAs and the development of GDM. Higher gestational weight gain was associated with a higher GDM risk (OR: 1.22, 95%CI: 1.01–1.48), when the FFAs difference was accounted for. Conclusions: FFA levels are higher in women with GDM compared with women with obesity or a normal weight. However, FFAs progressively decline from the first to the third trimester, with the most pronounced decrease in women with obesity, IR, and GDM.